Jazz in the Time of the Novel : The Temporal Politics of American Race and Culture - Barnhart, Bruce, 1966- (Book collections on Project MUSE., 2013)
Jazz in the Time of the Novel argues that a culture's understanding of the concept of time plays a central role in its economic, social, and aesthetic affairs and that a culture arrives at its conception of time through its artistic practices. Bruce Barnhart, in Jazz in the Time of the Novel, shows that American culture of the first three decades of the twentieth century was shaped by the kindred rhythms and movements of two particular art forms: jazz and fiction. At the beginning of the twentieth century, widespread changes in America's social, demogr.